Suplementos alimentares comercializados no Brasil: uma abordagem rotular, analítico e toxicológica - Dal Molin, Thaís Ramos (2019)
Consumption of dietary supplements has been increase worldwide, leading billionaires billing for Brazilian industries. Due to this situation, the National Health Surveillance Agency (Anvisa) has developed a new regulatory framework for dietary supplement, in order to regularize, to standardize and reduce the legal barriers of these products. This way, the present work aimed to acquired a certain number of samples marketed as food supplements, for a regulatory analysis, composition evaluation, investigation of the presence of adulterants and for a toxicological study. 44 samples of dietary supplements were purchased via the internet. From these, 97.7% showed irregular claims and 34.2% could not be commercialized as dietary supplements due their ingredients declared on the label. Still, regarding the centesimal composition, only 20 samples described the mandatory nutritional information on the label and, from these, 70% presented nutritional values above the tolerance allowed by the legislation. To investigate of the presence of adulterants in dietary supplements, a HPLC- DAD method was proposed for the determination of 10 non-permitted substances, with time of analysis less than five minutes. The proposed method was validated according to AOAC and Anvisa guidelines, and represented an economy of 40% when compared to LC-MS/MS, and the estimated cost for analysis was US$ 7.00 per sample. From 44 analyzed samples, seven contained at least one adulterant in their composition, such as diuretics, sexual stimulants and anabolic, for example. The adulterated supplements presented common characteristics, such as the acquisition in not specialized market, were imported from other countries, lack of information on the label and use of the claims that induced the presence of drugs in the composition. After this, an in silico prediction study was performed in order to compare with the in vitro cytotoxicity results, and thus, it was able to evaluate if the presence of the found substances is a determining factor for the increase of the toxicity in health cells. Despite the need for further studies regarding the sample matrix, the results indicate that there is a relationship between the multi-ingredients declared in the samples and the adulterants found, considering the cytotoxicity of the products. All seven samples presented cytotoxic effects, proportional to the concentration, by different mechanisms, either reducing cell viability, hemolysis or a significant increase of reactive oxygen species. Since the publication of the regulatory framework, the industries have five years to adapt to the new guidelines, however, is expected that the results shown here serving as a warning to both regulatory agencies and consumers for those irregularly sold products, or which ones that have some nonconformity in their label or even in their composition. The presence of adulterants in food supplements is a serious public health problem that can lead to irreversible health damage to those who consume them.